Intersectionality matters for Hispanic health: A replication study using the All of Us Research Program - Mariana Rodrigues; Emma Risner; Brennan Rhodes-Bratton; Stephanie H. Cook; Adolfo Cuevas (BMC, 2024)
Abstract Background Despite research dedicated to understanding the health profiles and health-related outcomes of Hispanic individuals, the prevailing body of literature frequently homogenizes the Hispanic population, failing to address the role of race in Hispanic health discourse. Thus, the current study applies an intersectional lens to identify health differences and similarities among Hispanic subgroups. Methods Sociodemographic characteristics and health domain variables (i.e., health status, health services, and health behaviors) from participants (N = 11,192) were included in the analyses. Bivariate Chi-squared tests examined the relationship between sociodemographic and health domain variables Black Hispanic individuals, white Hispanic individuals, and non-Hispanic Black individuals. Results Findings suggest that Non-Hispanic Black American individuals reported the highest rates of hypertension (49.09%) and diabetes (19.62%) compared to Black-Hispanic individuals (22.45% and 12.98%) and white Hispanic individuals (22.22% and 8.02%). Black Hispanic individuals reported the greatest proportion of asthma diagnoses (35.10%) and those who saw a doctor in the previous year (95.52%) compared to white Hispanic individuals (26.84%, and 91.10%, respectively) and non-Hispanic Black individuals ( 21.74%, and 94.69%, respectively). Conclusion Specifically, we found that several health behaviors and health-related outcomes significantly varied across different racial/ethnic groups, demonstrating the advantage of an intersectional approach to identify health disparities among racially diverse ethnic groups. Public Health significance We encourage the development of health care services with an awareness of the complexities resulting from racial differences within the Hispanic diaspora.